2016
DOI: 10.1111/wej.12196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recirculation rate of nitrified liquor and temperature on biological nitrification–denitrification process using a trickling filter

Abstract: In the modified Ludzack–Ettinger process, high‐energy input is required in a nitrification tank. To address this issue, a new biological nitrification–denitrification system was constructed with a trickling filter for nitrification. The effects of recirculation rate of nitrified liquor and temperature through the treatment of municipal wastewater were evaluated. The highest DN removal efficiency was observed at 6.5 h of hydraulic retention in the denitrification tank and 350% of recirculation rate of nitrified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the actual operation of urban sewage treatment plants in cold regions in winter, it was found that the activity of PAOs still exists in low-temperature environments; some inhibitory microorganisms grow rapidly, and nitrates have a strong inhibitory effect on anaerobic phosphorus release. Therefore, phosphorus removal capacity would have a certain tendency to decline under low-temperature conditions [4,52,53]. On the one hand, low temperature reduces the activity and metabolism of microorganisms in the anaerobic biological treatment process, which reduces methane production and COD removal efficiency.…”
Section: The Influence Of Temperaturementioning
confidence: 99%
“…In the actual operation of urban sewage treatment plants in cold regions in winter, it was found that the activity of PAOs still exists in low-temperature environments; some inhibitory microorganisms grow rapidly, and nitrates have a strong inhibitory effect on anaerobic phosphorus release. Therefore, phosphorus removal capacity would have a certain tendency to decline under low-temperature conditions [4,52,53]. On the one hand, low temperature reduces the activity and metabolism of microorganisms in the anaerobic biological treatment process, which reduces methane production and COD removal efficiency.…”
Section: The Influence Of Temperaturementioning
confidence: 99%
“…However, there is still a need for further studies that seek to increase its nitrification efficiency by effluent recirculation (Kanda et al 2016;Bressani-Ribeiro et al 2018) and to use new support media with larger specific area and low cost to replace gravel (Bressani-Ribeiro et al 2018). For this reason, several types of support media have been studied, from pall rings (Metcalf & Eddy, Inc. 2003) to alternative materials such as: corn cob, biochar, granular activated carbon, zeolites, slag, coal cinder, and tire rubber (Ali et al 2017;Forbis-Stokes et al 2018;Zhao et al 2013;Naz et al 2016).…”
Section: Introductionmentioning
confidence: 99%